A retrospective analysis of the incidence and risk factors for amniotic fluid embolism in cesarean deliveries - Xianghua Cao; Qiangjun Gui; Haoran Yan; Yujiao Wei; Xiaoling Chen; Deng Liang; Xueping Li; Jian Wang; Bingsha Chen (BMC Pregnancy and Childbirth)
Abstract Background Amniotic-fluid embolism (AFE) is a rare occurrence but life-threatening disease that can occur in process of delivery and postnatal women. The topic of cesarean section surgery and its associated risk factors has been neglected due to the infrequent occurrence of AFE. However, AFE significantly contribute to maternal morbidity and mortality. Purposes We aim to examine the correlation between clinical issues, prenatal complications, comorbidities, medical perioperative complications, and cesarean section surgery of AFE in the US, utilizing a Nationwide Inpatient Sample (NIS) database. Methods This study conducted a retrospective cohort analysis on cesarean deliveries in the United States using data from the NIS of the Healthcare Cost and Utilization Project (HCUP) to examine the incidence and risk factors of AFE during cesarean section surgery. The analysis included the period from January 1, 2010, to December 31, 2019. We employed a multivariable logistic regression to evaluate the main outcome, which encompassed the clinical, prenatal, comorbidity, and medical perioperative AFE undergoing cesarean deliveries. Results We identified AFE in 269 out of the 2,462,005 women whose cesarean deliveries we investigated, with an incidence rate of 0.0113%. In the AFE group, the median patient age at the cohort level was 32 years (IQR, 27–36 years). The in-hospital mortality rate for patients with AFE following cesarean delivery was significantly higher than for those without AFE (14.9% vs. 0.0%, P < 0.001). In univariable analysis, P < 0.05 served as the initial selection criterion. A multivariable analysis revealed that AFE at the time of cesarean deliveries was significantly correlated with chronic blood loss anemia, coagulopathy, congestive heart failure, other neurological disorders, fluid and electrolyte disorders, weight loss, pulmonary circulation disorders, abruptio placentae, and polyhydramnios. Conclusion This contemporaneous, nationwide investigation verified the incidence of cesarean deliveries by AFE and corroborated previously identified risk factors for AFE. Although the absolute risk of AFE is minimal, clinicians should be aware of the identified risk factors, such as chronic blood loss anemia, coagulopathy, and polyhydramnios, to enhance preparedness and optimize patient counseling, particularly in high-risk cases.